Isolating Colchicine in 19th Century: An Old Drug Revisited - Karamanou, Marianna; Tsoucalas, Gregory; Pantos, Konstantinos; Androutsos, George (Current Pharmaceutical Design, 2018)
Colchicine is a tricyclic alkaloid extracted from the herbaceous plant Colchicum autumnale. Known since antiquity for its therapeutic efficacy in the treatment of gout, colchicine was reintroduced in 19th century pharmacopeia, thanks to the work of the French chemists and pharmacists Pierre-Joseph Pelletier (1788-1842) and Joseph Bienaimé Caventou (1795-1877) who in 1819, isolated a peculiar substance in the roots of Colchicum autumnale. In 1833, the substance was further analyzed by the German pharmacist and chemist Philipp Lorenz Geiger (1785-1836), who coined the name colchicine. In 1884, the French pharmacist Alfred Houde (1854-1919) produced for the first time pure crystallized colchicine in granules of 1milligram which is still sold under this trade name in several countries. In the last two centuries, colchicine's indications were furthermore expanded. From anti-gout drug during antiquity and a diuretic in 19th century, colchicine is currently administered in several affections such as Adamantiades-Behcet's disease, familial Mediterranean fever, pericarditis and atrial fibrillation.
Keywords: joseph bienaimé caventou